Frontier research and innovation in optoelectronics technology and industry - Habib, Khaled; Lewis, E. (Elfed) (London, UK : CRC Press/Balkema, an imprint of the Taylor & Francis Group, 2019)
This book provides an overview of research achievements by industry experts and academic scientists in the subject area of Optoelectronics Technology and Industry. It covers a broad field ranging from Laser Technology and Applications, Optical Communications, Optoelectronic Devices and Integration, Energy Harvesting, to Medical and Biological Applications. Authored by highly-regarded researchers, contributing a wealth of knowledge on Photonics and Optoelectronics, this comprehensive collection of papers offers insight into innovative technologies, recent advances and future trends needed to develop effective research and manage projects. Researchers will benefit considerably when applying the technical information covered in this book.
Image processing : Improving the accuracy of stripe center extraction in a structured light measurement system / B. Chen, Y.J. Zhang & J.R. Zhang -- Deformation measurement of tooth-locked end closure flange of ultra high pressure vessel using digital image correlation method -- X.Y. Liu, Q.Y. kong, Y.G. Hou, Q. Guo, R.L. Li & C.J. Xu -- Single frame infrared image adaptive correction algorithm based on residual network / Mou, J. Lu, X. Zhou & X. Wang -- Development of an efficient computer generated synthetic hologram method -- Yang, Y. Li, Q.H. Yan, H. Wang, F.Y. Xu, J.H. Zhang & H.B. Zhang.
OCLC-licensed vendor bibliographic record.
Keywords: Optoelectronic devices -- Research; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY / Lasers